Are Laboratory Parameter (Biomarker) Values Similar to the Healthy Volunteer Reference Range in Individuals with Diabetes - Brott DA; Goodman MJ; Hermann RP; Anderson I; Kiazand A (Dove Medical Press, 2020)
David A Brott,1 Michael J Goodman,1 Richard P Hermann,1 Isobel Anderson,2 Alexandre Kiazand1 1Patient Safety Center of Excellence, Chief Medical Office Organization, AstraZeneca Pharmaceuticals, Gaithersburg, MD, USA; 2Patient Safety Center of Excellence, Chief Medical Office Organization, AstraZeneca Pharmaceuticals, Macclesfield, UKCorrespondence: David A BrottTakeda Pharmaceuticals, 300 Massachusetts Avenue, Cambridge, MA, USATel +1 3042408302Email David.Brott@Takeda.comBackground: Identification of laboratory parameter clinical safety signals depends on the terminology and scoring criteria. Grade 1 scoring criteria in the Common Terminology Criteria for Adverse Events (CTCAE) is typically based on the healthy volunteer reference range (HVRR). The objectives of this study were to determine 1) what laboratory parameters in individuals with diabetes are potentially different from the HVRR and 2) what fold change from baseline should be expected in this population.Materials and Methods: Baseline data from the individuals with diabetes clinical trial data (TransCelerate dataset) were compared to the HVRR using a 10% threshold above HVRR to classify laboratory parameters as potentially different from the HVRR. These parameters were then evaluated longitudinally to determine the expected x-baseline values for individuals with diabetes for potential use in identifying drug-induced changes.Results: The baseline data determined that 28% of the laboratory parameters evaluated were potentially different from the HVRR. Longitudinal data analysis determined 1) thresholds for 13 of these laboratory parameters with the subjects above the threshold having greater variability than those below the threshold, and 2) the expected upper limits (x-baseline) were calculated for the laboratory parameters. For example, a 1.8– 2.6 x-baseline value for alanine aminotransferase, depending on how the baseline is calculated, is expected in individuals with diabetes.Conclusion: It is not uncommon for laboratory parameters in individuals with diabetes clinical trials to be potentially different from the HVRR, and the x-baseline criteria for 13 of these laboratory biomarkers was determined for this population. This suggests consideration in modifying the current CTCAE grade 1 criteria of > 1.5– 3.0 x-baseline should be further investigated as to if the current criteria detects too many false-positive signals in this population.Keywords: diabetes, biomarkers, reference range, laboratory parameter, pharmacovigilance